(untitled) (Journal of Parents and Teachers, 2018)
In the process of teaching and learning mathematics, experimentation activities play a fundamental role, because, in an environment based on shared learning and through the use of hand-on materials, they allow students to build mathematical knowledge at the same time that, from practice, mathematical competences are developed. From eight reflections we show the need to promote, in our opinion, the use of this type of activities in mathematics education.